207k views
3 votes
Let g(x) = 2x2 - 11x. Find g(1).
A) -13
B) -9
C) 9
D) 11

User Raylu
by
4.3k points

2 Answers

4 votes

Answer:

(B) -9

Explanation:

g(x) = 2x² - 11x

To find g(1), we substitute x = 1 into g(x).

g(x) = 2x² - 11x

g(1) = 2(1)² - 11(1) = 2 - 11 = -9

User Bharat Vasant
by
5.4k points
3 votes

ANSWER

B) -9

EXPLANATION

The given function is


g(x) = 2 {x}^(2) - 11x

Put x=1 into the given function to obtain;


g(1) = 2 {(1)}^(2) - 11(1)

Simplify to get:


g(1) = 2 (1) - 11(1)


g(1) = 2 - 11 = - 9

The correct choice is B.

User Andrew Hardiman
by
5.3k points